Populism in the liberal democracies of East Asia: South Korea, Japan, and Taiwan - Hannes B. Mosler (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2023)
In recent decades, the surge of populist movements and leaders has captivated the attention of scholars, policymakers, and the general public around the world. The rise of populism and populists has prompted a profound reevaluation of the dynamics within democratic societies and the complex interplay between political, social, and economic forces. As this phenomenon continues to evolve, it has ignited intense academic debates, sparking a quest to understand its manifestations, causes, and implications across diverse socio-political contexts. This collection of working papers embarks on a hitherto unique journey, focusing its analytical lens on the enigmatic landscape of the potentialities of populism within the East Asian liberal democracies of South Korea, Japan, and Taiwan. Each paper in this collection engages with specific cases, delving into the intricate web of the political, cultural, and social nuances that shape the trajectory of populism within these countries. However, these papers do not merely stand as isolated studies; they are embedded within a larger academic discourse, contributing to and enriching the broader dialogue on the nature and implications of populism.
Keywords: 330; Democracy; Liberalism; Populism; Japan; South Korea; Taiwan; Demokratie; Liberalismus; Populismus; Japan; Südkorea; Taiwan